LEGAL PROTECTION OF GEOGRAPHICAL INDICATIONS AS AN INSTRUMENT TO INCREASE THE COMPETITIVENESS OF LOCAL PRODUCTS IN INDONESIA - Andry Dwiarnanto; Evita Isretno Israhadi (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2026)
Indonesia's juridical safeguards for Geographical Indications expose pronounced disparities between statutory constructs and execution realities. This inquiry dissects GI protection regimes normatively and comparatively, delineates regulation-implementation chasms (das sollen versus das sein) with attendant barriers, and proposes a tactical GI safeguard paradigm elevating Indonesian regional goods' global market prowess. Adopting normative juridical inquiry via statutory, doctrinal, and cross-jurisdictional methods, results affirm Law Number 20 of 2016 on Marks and Geographical Indications furnishes TRIPs-conformant comprehensive protections. Implementation, however, falters amid lax post-grant oversight, producer communities' juridical ignorance, provincial authorities' institutional shortfalls, and vast untapped local product potentials. These deficits curtail GIs' catalytic impact on competitiveness. An encompassing tactical paradigm—fusing registration bolstering, tech-enabled post-registration administration, and enduring multi-actor symbiosis—proves requisite.